From iconoclast to traditionalist : a study of Anatolii Efros's productions of Chekhov, Gogol and Turgenev - Dixon, Ros (2003)
Between 1951 and 1987 the Russian director Anatolii Efros created seventy four stage productions, thirteen television films, four feature films and four radio plays. His work made a significant contribution to the development of Russian theatre in the twentieth century, but has received no comprehensive study in Russian or English.